2020
DOI: 10.1093/jscr/rjaa280
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection presenting with acute epiglottitis

Abstract: In this case report, we present a novel presentation of acute epiglottitis in a patient with severe acute respiratory syndrome—coronavirus 2 (SARS-CoV-2) who presented to the emergency room in extremis and respiratory failure requiring emergent cricothyrotomy. Epiglottitis has become less common since the introduction and widespread use of the Haemophilus influenzae type B (Hib) vaccine. This reduction in cases has shifted demographics of the disease from the pediatric population towards adults with comorbid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 3 publications
0
25
0
1
Order By: Relevance
“… 5 Fondaw et al reported a case of COVID-19 presenting with upper airway obstruction due to acute epiglottitis requiring emergency surgical cricothyroidotomy. 6 Our case could have been a varied presentation of COVID-19. Considering that this occurred in beginning of the COVID-19 pandemic, there arises a suspicion whether SARS-CoV-2 could have caused this.…”
Section: Discussionmentioning
confidence: 84%
“… 5 Fondaw et al reported a case of COVID-19 presenting with upper airway obstruction due to acute epiglottitis requiring emergency surgical cricothyroidotomy. 6 Our case could have been a varied presentation of COVID-19. Considering that this occurred in beginning of the COVID-19 pandemic, there arises a suspicion whether SARS-CoV-2 could have caused this.…”
Section: Discussionmentioning
confidence: 84%
“…Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is a rapidly progressing respiratory disease that also affects the upper aerodigestive tract via angiotensin-converting enzyme 2 or transmembrane protease/serine subfamily member 2 receptors [ 1 , 2 ], causing a sore throat and odynophagia. There are reports of COVID-19-induced acute laryngitis requiring emergency treatment, indicated by acute epiglottitis in adults and croup in infancy [3] , [4] , [5] , [6] , [7] , [8] , [9] . Frequently, this requires urgent airway management, which generates aerosols and increases the risk of spreading the infection.…”
Section: Introductionmentioning
confidence: 99%
“…Cases of acute epiglottitis associated with COVID-19 are exceedingly rare – to our knowledge, there have been two cases reported in the literature, described by Fondaw et Al. in September 2020 [ 2 ], and by Alqaisi et Al. in January 2021 [ 3 ].…”
Section: Introductionmentioning
confidence: 99%